(untitled) (Jurnal Bahasa, 2001)
This article intends to show that Malay pronunciation is sensitive to certain social variation. Furthermore, this article also concerns to the matter of codification of pronunciation since it is a prominent problem in standard Malay. The issue is proven through a sociophonological research in school. The two social variables which is considered in this article are speech style and nativeness of the subject.